The usage of the Mashbooh ingredients in the pharmaceutical industry: a review - Mokhtar, Asma'; Jamaluddin, Nor Sabirah Najihah; Ahmad Fadzillah, Nurrulhidayah; Zainan Nazri, Nurul Jannah (Globeedu Group, 2019)
The global Halal pharmaceutical market, which accounted for 6.7% of the global pharmaceutical market two years ago is expected to reach US$370 billion in size in 2021 by showing an average annual growth of 9.3%. Along with the advancement of science and technology, the raw materials or ingredients can be obtained from many different sources which the status can be Halal, Haram or Mashbooh. This is why Islam is very particular when it comes to the matter of raw materials or ingredients. However, study on the Mashbooh ingredients seems scanty to be found. The objective of this study is to understand the dilemma of the usage of the Mashbooh ingredients in the pharmaceutical industry. It will discuss about the common Mashbooh ingredients used in the pharmaceutical industry along with Islamic perspectives related to Mashbooh ingredients. The primary source will be used in this study is library research through reviewed literatures and documents pertaining to the objective. Hence, this study signifies the importance of understanding the usage of the Mashbooh ingredients in the pharmaceutical industry